Digital Literacy for Teachers - Tomczyk, Łukasz; Fedeli, Laura, 1958- (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book shows the results of research in different countries on how to measure digital competence among future generations of teachers and facing the challenges brought by the convergence of analogue and digital media. This book provides answers to the research questions: How should the key competencies related to media pedagogy be effectively measured and compared? What is the level of digital literacy of pre-service teachers in selected countries? The individual chapters are based on a systematic review of research results (from the last two decades) to show trends related to changes in measurement and levels of digital competence. This book is valuable for researchers training future generations of teachers inthe use of new media as well as to those trying to measurethe development of the information society, as well as those conducting research in the field of comparative pedagogy (including the transfer of the most effective solutions in the field of media pedagogy)
Includes bibliographical references.
Keywords: Educational technology; Teachers-Training of